IMPLEMENTATION OF SAK EMKM IN FINANCIAL TRANSACTION RECORDING AND COST MANAGEMENT PRACTICES OF AUTOMOTITVE SERVICE MSMEs: A CASE STUDY OF IJUN JOK MOBIL - Alya Sahbrina; Hendra Harmain; Yenni Samri Juliati Nasution (JAT : Journal Of Accounting and Tax, 2026)
This study aims to analyze the implementation of financial transaction recording and business cost management based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in supporting financial management at the Ijun Jok Mobil automotive service MSME. This study employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, and analyzed descriptively by comparing existing financial recording practices with the provisions of SAK EMKM. The results showed that prior to the implementation of SAK EMKM, financial recording was still limited to recording cash inflows and outflows without preparing systematic financial statements. After the preparation of financial statements based on SAK EMKM, including an income statement, statement of financial position, and notes to the financial statements, the business obtained more accurate and transparent financial information, with a net profit of Rp15,358,333 for the October 2025 period. The study also found that low accounting literacy and limited human resources were the main obstacles to implementing SAK EMKM. Therefore, improving accounting understanding and providing continuous assistance are necessary to support the sustainable implementation of accounting standards in MSME financial management. This study contributes to the literature by providing empirical evidence regarding the implementation of SAK EMKM in automotive service MSMEs, which have more complex cost structures than trading businesses. The findings imply that the implementation of SAK EMKM can improve financial transparency, support managerial decision making, and enhance business sustainability among MSMEs.